ANALYSIS OF THE IMPLEMENTATION OF ASEAN STANDARD HOMESTAY IN HANJELI TOURISM VILLAGE SUKABUMI REGENCY - Eka Nuraisah Rosiana; Siti Yulia Irani Nugraha; Wildan Rizky Rahadian; Nisa Rahmaniyah Utami (Bogor Hospitality Journal, 2025)
Homestay is one of the amenities available in tourist villages as a place to stay for visiting tourists. Homestays have the advantage of offering cheap prices and a stay experience that cannot be obtained when staying at a hotel. Even though a homestay is basically an ordinary house that is rented out by the owner to tourists, a homestay must still have several criteria that are met as eligibility requirements to become a homestay. This research aims to present data and information regarding the implementation of ASEAN homestay standards in Hanjeli village, Sukabumi using qualitative methods by conducting observations and interview with informants, namely homestay owners and tourist village managers. Based on the results of the research that has been conducted, the level of achievement of the implementation of ASEAN homestay standards in Hanjeli Tourism Village has not reached 100%.